Multilateral Trade Cooperation: What Next? - Hoekman, B; Vines, D (2007)
This paper first briefly describes the role of the WTO and its history. It then lays out a simple bargaining model of international negotiations, which can be used for understanding the Doha Round of talks. Using this, we distil what we regard as the major potential explanations for the difficulties in these talks. We then discuss a number of the systemic questions that confront WTO members. We suggest that the WTO should concentrate on market access, rather than on promoting a development agenda or on further expanding its coverage to deal with regulatory issues or with other domestic policies.